Anterior and posterior complexes: a step towards improving neurosonographic screening of midline and cortical anomalies. (12th October 2015) - Viñals, F.; Correa, F.; Gonçalves‐Pereira, P. M.
Abstract: Objective: To describe the anatomical structures that form the anterior (AC) and posterior (PC) complexes of the fetal brain and to categorize their anomalies in fetuses with cerebral abnormalities. Methods: We analyzed retrospectively volume datasets from 100 normal fetuses between 20 and 30 weeks' gestation. On the axial transventricular plane, our analysis of the AC included the interhemispheric fissure (IHF), the callosal sulcus (CS), the genu of the corpus callosum (CC), the cavum septi pellucidi (CSP) and the anterior horns (AH) of the lateral ventricles. The PC included the splenium of the CC, the medial wall of the lateral ventricles, the CS and the parieto‐occipital fissure (POF). We then categorized AC/PC findings in 32 fetuses with agenesis of the septi pellucidi, schizencephaly, callosal dysgenesis, cortical malformation and hypoxic‐ischemic brain injury. Results: The structures forming the AC and PC were visible in 100% and 92%, respectively, of normal cases. In the AC, the CSP was square‐shaped in 73% of cases and it was triangular in 27%; the AH was comma‐shaped in 92% of cases and triangular in the remainder. In the PC, the splenium of the CC interrupted and bridged the midline and was delimited posteriorly by the CS and the IHF. The POF was visible posteriorly. We categorized AC and PC abnormalities according to the main deviation from normality in their anatomical structures. The AC was abnormal in 30/32 cases and the PC was abnormal in 16/32 cases. In the two cases with normal AC, the PC was abnormal. Conclusion: Normal appearance of AC and PC seems to be a strong indicator of fetal central nervous system normality. Morphological abnormalities in both complexes are robust markers of midline defects, but not exclusively so. The majority of fetuses with cortical malformations showed a defect in the AC. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.